Results for World Rowing Federation and Olympic events 1893-2019 - Fischer, M.; Secher, N. H. (Research in Sports Medicine, 2022)
Results in rowing have improved and here we estimate results for Olympic and World rowing championships based on the winning results from 1893 to 2019 obtained in the current seven Olympic events for men (n=556) and women (n=239). Data were collected from the official World Rowing Federation online records and from published results and the development analysed by linear regression analysis for the year of competition. Results improved by about 0.7 s per year (15±9.4%) (mean ± SD). Depending on the event, 2020 predicted mean time for the winning boat for men is 363 s (range 326-397) vs. 404 s (362-439) for women (10.3±1.1% slower). The ten-year coefficient of variance for the original boats in Olympic and World Rowing Federation regatta remaining within the Olympic programme, single scull and eight, decreased from 9±2% (1893-1903) to 2±0.4% (2009-2019). Reduced variability in winning times illustrates the standardization of the rowing course and boats, and the improvement in performance point to that body size becomes ever more important for success in competitive rowing.